Ali je lahko ženska Kolumb? Nekateri vidiki preučevanja potopisov Alme Karlin - Bodrova, Anna (Slavia Centralis, 2020)
CAN A WOMAN BE A COLUMBUS? SOME ASPECTS OF ALMA KARLIN'S TRAVELOGUESThe paper deals with some disputable aspects of Alma Karlin’s travelogues, which play an important role in her work. The genre characteristics of her travelogues, their literary topics and the autobiographical nature are considered. Particular attention is paid to both the goals of Alma Karlin’s journey and intentions of her travelogues. The basic focus is on the specifics of women’s travel and the phenomenon of the border, which is problematised not only by Karlin’s works, but also by their reception. The motif of horror, which is partly relevant to trivial literature, is also examined, and the female version of the archetype of the hero as discoverer, as is presented in the works of A. Karlin, is discussed.
Keywords: Alma Karlin; travelogue; women’s travel; border